2016
DOI: 10.1097/rct.0000000000000329
|View full text |Cite
|
Sign up to set email alerts
|

Non–Electrocardiogram-Triggered 70-kVp High-Pitch Computed Tomography Angiography of the Whole Aorta With Iterative Reconstruction

Abstract: Non-ECG-triggered 70-kVp high-pitch aortic CTA with IR provides equivalent diagnostic image quality with 90% reduction of radiation dose and 25% reduction of contrast volume compared with standard 120-kVp CTA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…The CTA at low tube voltages (low-kV imaging) has been investigated as a tool to increase CT attenuation and the contrast-to-noise ratio (CNR) of the aorta with the option of radiation dose and/or CM reduction 18–30 . Following these lines, automatic tube voltage selection (ATVS) has been introduced as a means to reduce radiation dose in CT depending on the imaging task and patient habitus, while maintaining image quality in terms of the CNR 31 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The CTA at low tube voltages (low-kV imaging) has been investigated as a tool to increase CT attenuation and the contrast-to-noise ratio (CNR) of the aorta with the option of radiation dose and/or CM reduction 18–30 . Following these lines, automatic tube voltage selection (ATVS) has been introduced as a means to reduce radiation dose in CT depending on the imaging task and patient habitus, while maintaining image quality in terms of the CNR 31 .…”
mentioning
confidence: 99%
“…17 The CTA at low tube voltages (low-kV imaging) has been investigated as a tool to increase CT attenuation and the contrast-to-noise ratio (CNR) of the aorta with the option of radiation dose and/or CM reduction. [18][19][20][21][22][23][24][25][26][27][28][29][30] Following these lines, automatic tube voltage selection (ATVS) has been introduced as a means to reduce radiation dose in CT depending on the imaging task and patient habitus, while maintaining image quality in terms of the CNR. 31 The ATVS system has primarily been designed for radiation dose optimization by selecting the tube voltage level that offers lowest radiation dose at maintained CNR.…”
mentioning
confidence: 99%
“…[14][15][16]43 Beeres et al 14 applied the CM volume of 90 ml in high-pitch dual-source aortic CTA and obtained good image quality. Using low kVp settings in high pitch mode, Shen et al 15 and Zhang et al 43 attempted to reduce CM dose to the weightadapted volume of 1.0 ml kg 21 (270 mgI kg 21 ) and the fixed volume of 60 ml, respectively. As for volume acquisitions, Chen et al 16 proposed the joint application of wide-volume CT and iterative reconstruction algorithm to lower the CM volume to 40 ml in aortic CTA.…”
Section: Discussionmentioning
confidence: 99%
“…One study showed that it was possible to reduce the CM volume in a CTA by 25% by scanning at 70-kVp using a high-pitch technique with the same diagnostic accuracy as compared with standard 120-kVp and standard volume of CM. [23] Another study showed that low tube voltage 80 kVp CTA using 50 mL of CM has the same diagnostic quality as a 120 kVp CTA using 100 mL of CM. [24] Patient body weight can use to determine the optimal Figure 8: 84-year-old female presenting to the emergency department after an unwitnessed fall and acute blood loss anemia with a concern for acute aortic injury.…”
Section: Kilovoltage (Kvp) and Masmentioning
confidence: 99%